The Advantages of Using an Analytic Scoring Procedure in Speaking Assessment - Nur Mukminatien (TEFLIN Journal: A publication on the teaching and learning of English, 2000)
Abstract: This article describes the advantages of using analytic proceÃÂdure in speaking assessment. An analytic scoring guide, as compared to the impressionistic one, has a double function: as an instrument to meaÃÂsure the learners speaking proficiency and as a diagnostic procedure for remedial teaching. Thus, it provides reliable sources of information in the form of scores of the speaking components and can be used as feed-back for the teacher and learner to identify which component needs imÃÂprovement.